Doświadczenia wybranych państw członkowskich Unii Europejskiej w zakresie migracji powrotnych - Maciej Dustczyk (University of Warsaw, Centre of Migration Research (CMR), 2007)
– Throughout the history of the European Union quite a few cases of transformation of typical emigration countries into countries of both emigration and immigration have been noted. This regards Italy (end of 60s/beginning of 70s), Ireland (end of 80s/beginning of 90s), Greece (in the 80s) and Spain and Portugal (in the 90s), especially. Such transformation of these countries was directly related to their acquisition of EU-membership. In the case of all the countries, gaining EU-membership ultimately resulted in a fall in the level of emigration and the phenomenon of return migration. However, there were noticeable variations in the time frame within which the latter process took place in a given country. The economic situation of the country, and especially prognoses as to the situation on the labour market, appears to be a decisive factor in shaping the process of return migration. Also political factors, inter alia connected with the perception of the direction in which the country was proceeding, proved to be of crucial importance. The experiences of other European countries may be analysed with a view to ascertaining the current standing of Poland. At the same time, however, it must be underlined that the Greek, Spanish and Portuguese cases differed greatly from the Polish one in terms of the duration of the transition periods for the free movement of labour, which were considerably longer than for Poland. Hence, definite conclusions as to the Polish case cannot be drawn on the basis of this analysis, particularly with reference to the time-frame within which return migration tom Poland might start taking place. Considering the current situation of Poland, the Spanish case appears the most analogous.
Keywords: 330; Rückwanderung; Internationale Migration; EU-Mitgliedschaft; EU-Staaten